Historical aspects of the iron-cementite diagram - Костик, Виктория Олеговна (Technology audit and production reserves, 2014)
The purpose of the research lies in generalizing, improving and supplementing an iron-cementite diagram. The aim was to study historical aspects of the diagram. The method of solving the problem was to find the lost and forgotten historical facts. An improved phase diagram of iron-cementite conditions is given in the paper. The novelty of this diagram lies in combining phase transformations, structural components and glow colors at different temperatures and concentrations of the components that allows obtaining the maximum amount of information by using the diagram. A historical aspect of the diagram was also studied, the origin of names of phases and structural components was considered as well. The diagram of iron-carbon has a great practical value and gives the basis for studying the processes of treating iron and steel with heat. It is used for determining the types of heat treatment, temperature ranges of transformations, etc. In addition, the diagram can be used for predicting the microstructure at any preset temperature.